Geomorphometric assessment of drainage systems in a semi-arid region of Argentina using geospatial tools and multivariate statistics - Genchi, Sibila Andrea (2016)
In semi-arid environments there is often a lack of data on hydrological variables that limits the ability to understand key hydrological processes. In response to this need, geomorphometric analysis is a quantitative approach that has proven to be useful. This work aims to assess and classify 35 exorheic drainage basins located in a semi-arid area of Argentina (Northeastern Patagonia) according to their geomorphometric properties by using GIS technology and principal component (PCA) and cluster analysis (CA) multivariate techniques. In addition, an assessment of automated drainage network extraction accuracy was performed by comparing it with the actual drainage network. The study showed that it was possible to derive automated drainage networks with errors lower than 6 %. By comparing both PCA and CA, it was found that the former allows a good understanding of the clustering of basins from the CA. All basins were clustered into four groups following a significant spatial continuity. This type of study gives the basis for regionalscale analysis, and provides further information for subsequent modeling.